Fluorescence chemosensing of meldonium using a cross-reactive sensor array. Issue 9 (30th March 2020) - Yalcin, Ergin; Erkmen, Cem; Taskin-Tok, Tugba; Caglayan, Mehmet Gokhan
Abstract : Differential sensing of meldonium was achieved using fluorescent chemosensors. Abstract : In this paper, we report a fluorescent sensor array approach for the urinary detection of a prohibited substance in sports, meldonium. Four chemosensors with ethidium bromide scaffolds were employed in this method. The interaction between meldonium and chemosensors was investigated by different techniques, such as ultraviolet-visible absorption and fluorescence spectroscopy, nuclear magnetic resonance, and mass spectrometry. Molecular dynamics simulation was also used to elucidate and support the interaction mechanisms between meldonium and the chemosensors. Differential responses obtained from the sensor array enabled the qualitative and quantitative analyses of meldonium with low error values. This method was able to detect and quantify meldonium at the nM level, fulfilling the requirements of minimum performance defined by the World Anti-Doping Agency.